2010
DOI: 10.1111/j.1750-3841.2010.01877.x
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic Hydrolysis of Blue Whiting (Micromesistius poutassou); Functional and Bioactive Properties

Abstract: Functional and biochemical properties of fish protein hydrolysates (FPH) from blue whiting (BW) were studied. FPH (2.5%, 5%, 10%, and 15% degree of hydrolysis [DH]) were made from isolated proteins from headed and gutted BW with Alcalase 2.4 L. The properties of dried BW mince and protein isolate compared to 4 reference proteins (soy and milk protein) were studied: color, solubility, water-holding capacity (WHC), oil-binding capacity (OBC), emulsion capacity (EC), and emulsion stability (ES). The angiotensin I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
39
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(54 citation statements)
references
References 42 publications
14
39
0
Order By: Relevance
“…Additionally, the balance of hydrophilic and hydrophobic forces of peptides is also mentioned as an important cause of solubility enhancement (Kristinsson and Rasco, 2000;Gbogouri et al, 2004). Several reported studies have also confirmed that increasing DH increases solubility of protein hydrolysates (Quaglia and Orban, 1987;Chobert et al, 1988a, b;Mutilangi et al, 1996;Linar es et al, 2000;Gbogouri et al, 2004;Klompong et al, 2007;Souissi et al, 2007;Balti et al, 2010;Geirsdottir et al, 2011). The solubility of the hydrolysates is especially improved at the proteins isoelectric point, pI (Chobert et al, 1988b).…”
Section: Solubilitymentioning
confidence: 61%
See 2 more Smart Citations
“…Additionally, the balance of hydrophilic and hydrophobic forces of peptides is also mentioned as an important cause of solubility enhancement (Kristinsson and Rasco, 2000;Gbogouri et al, 2004). Several reported studies have also confirmed that increasing DH increases solubility of protein hydrolysates (Quaglia and Orban, 1987;Chobert et al, 1988a, b;Mutilangi et al, 1996;Linar es et al, 2000;Gbogouri et al, 2004;Klompong et al, 2007;Souissi et al, 2007;Balti et al, 2010;Geirsdottir et al, 2011). The solubility of the hydrolysates is especially improved at the proteins isoelectric point, pI (Chobert et al, 1988b).…”
Section: Solubilitymentioning
confidence: 61%
“…During enzymatic hydrolysis, the presence of polar groups (-COOH and -NH2) increases, and it is assumed that this has a substantial effect on the increased WHC observed for hydrolysates (Balti et al, 2010). However, others stated that the DH did not affect the WHC (Geirsdottir et al, 2011). Additionally, Choi et al (2009) observed higher WHC of the insoluble fraction of protein hydrolysates than the soluble fraction.…”
Section: Gelling Propertiesmentioning
confidence: 92%
See 1 more Smart Citation
“…products like squid generally contained a high amount of protein where the majority of it composed with myofibrilar protein (80%), followed by myoplastic protein (12-20%) and the least was myostroma protein (2 -3%) which composed of collagen (Okuzumi and Fujii, 2000). The ability of the protein to function as an ingredient in food products depends on their functional properties such as amino acid composition and environmental factors including pH, temperature and ions present (Geirsdottir et al, 2011). The value of fat content in squid ink powder is slightly higher compared with raw squid which was about 1.0 to 2.0%, where the value considered lowest among all types of seafood (Okuzumi and Fujii, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…As the acid denaturation reactions do not break the peptide bonds, the amino acid sequence remains the same (Fink et al 1994, Uversky andYuji, 2009). Alternatively, enzyme hydrolysis of protein cleaves peptide bonds, resulting in compounds of reduced molecular size (Geirsdottir et al, 2011;Jaenicke and Rudolph, 1990;Uversky and Yuji, 2009). Smaller peptide chains and FAAs are generally considered easier to absorb and thus increase the level of amino acids available for protein accretion (Buxbaum, 2007;Kaushik and Seiliez, 2010;Kvale et al, 2002).…”
Section: Introductionmentioning
confidence: 97%